THE INFLUENCE OF MOTIVATION ON THE DECISION MAKING OF STARTING A SMALL BUSINESS (CASE STUDY OF COMMUNITIES IN BELOPA UTARA DISTRICT, LUWU DISTRICT) - Muh. Shadri Kahar Muang (Al-Amwal : Journal of Islamic Economic Law, 2022)
This study discusses motivation and decision-making to start a small business (a case study of a community in North Belopa District, Luwu Regency). The formulation of the problem in this study is whether motivation influences the decision making of starting a small business in North Belopa District. The purpose of this researchTo knowdoes motivation affect the decision making of starting a small business in North Belopa District, Luwu Regency. The type of research used is quantitative research. The population is small business actors in North Belopa District, totaling 450 people. Part of the population is used as a sample. Withdrawal of samples with simple random technique, collecting data with a questionnaire. Data analysis using simple linear regression analysis with the help of SPSS Version 15. The results of this study indicate that there is a significant influence between motivation in decision making. This is evidenced by the value tcount =5,605> ttable = 1.664 and a significance value of 0.000 <0.05. These results are consistent with the hypothesis (H1) which states that there is an influence between motivation and decision making. The effect of motivation on decision making is 21.5%. The implications based on the research results obtained in the community in North Belopa District, Luwu Regency in this study are for the people of North Belopa District to always increase their business motivation.